2008
DOI: 10.1091/mbc.e08-04-0426
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Golgi Network and Endosome Dynamics Connect Ceramide Homeostasis with Regulation of the Unfolded Protein Response and TOR Signaling in Yeast

Abstract: Synthetic genetic array analyses identify powerful genetic interactions between a thermosensitive allele (sec14-1ts ) of the structural gene for the major yeast phosphatidylinositol transfer protein (SEC14) and a structural gene deletion allele (tlg2⌬) for the Tlg2 target membrane-soluble N-ethylmaleimide-sensitive factor attachment protein receptor. The data further demonstrate Sec14 is required for proper trans-Golgi network (TGN)/endosomal dynamics in yeast. Paradoxically, combinatorial depletion of Sec14 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 110 publications
2
50
0
Order By: Relevance
“…In addition to its involvement in the Cvt pathway, Tlg2p is a syntaxin-like t-SNARE that participates in vesicle fusion, endocytosis, Golgi complex-to-vacuole transport, endosomal protein sorting, and protein release from the endoplasmic reticulum (1,10,18,20,35,41). Mousley and colleagues previously showed that Tlg2p has a role in protein secretion in combination with Sec14p (35), and our results suggest that the participation of Tlg2p in the secretion of Eno2p is plausible. Therefore, we conclude that the secretory pathway of glycolytic enzymes is regulated in a different manner from the Cvt pathway.…”
Section: Discussionsupporting
confidence: 59%
“…In addition to its involvement in the Cvt pathway, Tlg2p is a syntaxin-like t-SNARE that participates in vesicle fusion, endocytosis, Golgi complex-to-vacuole transport, endosomal protein sorting, and protein release from the endoplasmic reticulum (1,10,18,20,35,41). Mousley and colleagues previously showed that Tlg2p has a role in protein secretion in combination with Sec14p (35), and our results suggest that the participation of Tlg2p in the secretion of Eno2p is plausible. Therefore, we conclude that the secretory pathway of glycolytic enzymes is regulated in a different manner from the Cvt pathway.…”
Section: Discussionsupporting
confidence: 59%
“…A constant (targeted) flux of secretory vesicles, and a balancing flux of endocytic vesicles to recover membrane material are required for cellular remodeling as well as for cell growth (Araujo-Bazan et al, 2008;Higuchi et al, 2009;Kohli et al, 2008;Zonia and Munnik, 2008), also in Saccharomyces (Ayscough, 2005;Moreira et al, 2009;Walther et al, 2006). This appears central for maintenance of cellular homeostasis (Mousley et al, 2008). The high variability of the fitness effects of these mutant groups was not mimicked by a high variability of their transcription.…”
Section: General Requirements For Adaptationmentioning
confidence: 97%
“…It is also possible that Avl9 and Gtr proteins have a role in regulating plasma membrane homeostasis, or an Avl9-and Gtr-dependent sorting or transport process depends on optimized lipid composition. There is much evidence that regulation lipid composition is critical for cargo sorting and transport carrier formation in the late secretory pathway (21,23,24,30,41).…”
Section: Discussionmentioning
confidence: 99%
“…In our samples, we did not observe the very large rings seen in the arf1⌬ mutant. However, the arf1⌬ and sec14-ts mutants have defects in transport from both Golgi and endosomes (15,23), and the invertase-transporting exocytic pathway likely transits endosomes (17), so our group A compounds could perturb exit from either or both the Golgi and endosomes. Wild-type cells had a similar but less abundant membraneaccumulation phenotype when grown in the presence of KU#7 (Fig.…”
Section: Vol 9 2010 Exocytic Inhibitors In Yeast 119mentioning
confidence: 99%